A study on the Surface Roughness of Galvannealed Low Carbon Al-Killed and Ti-Nb Stabilized Interstitial Free Steels - Elkoca, Candan Sen; Ekmekci, Bulent; Elkoca, Oktay (Archives of Metallurgy and Materials, 2021)
In this study, the surface roughness of galvannealed low carbon Al-killed and Ti-Nb stabilized interstitial free steels was investigated using the industrial galvannealing process parameters. The iron content of the coatings was also analysed to establish a relationship with the surface roughness and coating composition. The surface roughness displayed an exponential behaviour with increasing of annealing time at each annealing temperature in both steel coatings, which was in an increasing order in the galvannealed low carbon Al-killed steel coating, whereas it was a reverse order in the galvannealed Ti-Nb stabilized interstitial free steel coating. The craters were observed on the galvannealed coatings resulting in high surface roughness. Increasing the iron content of the coatings leads to a reduction in the surface roughness with δ1k phase.
Keywords: Galvannealing; galvannealed steel; hot-dip galvanizing; Fe-Zn phases; surface roughness